(3cJGH GdfMhs - (3GdMSf Hf eMeO GdCUHgGfj, CHh Ydj GdeYQha HdZOI, Ch dZPI Ch dcPI, hdYdg HGdcGa GdeYbhOI,J (B311 (3g` s
(3ChdgG (B:s
(3GdcdGe cdeI KdGKI CTjGA (B: (3GSe haYd hMQa LGA deYfi djS HGSe hdG aYd s
(3BNQgG (B:s
(3aJbhd ai GdfSH Edi GdeOGFf (B: (3eOGFfi , dCfg GSe dHdO hEdi cdGH hCfeGQ hVHGH EPG cGfJ GSekG ddbHGFd hGdCMjGA (B: (3cdGHi hVjGHi hCfeGQi GfbVi cJGH GdfMh s
(3GdfSNI HgG MhGTs
(3ajeG Hjf SWhQgG RjGOGJ dCHi YeQ GdUHGZs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B212 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B238s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(100 / 5 (3b(B) s
Keywords: (3GdfMhs